Perancangann Alat Angkat Mesin Mobil Sistem Hidrolik - Aswar, Muh; Sisworo, Raden Rinova; Samhuddin, Samhuddin (Teknik Mesin Universitas Halu Oleo, 2022)
This lifting device is for lifting and lowering loads supported by truss mechanism and a hydraulic jack with a maximum lifting capacity of 480kg. The device focuses on lifting the car engines with a lifting mechanism consisting of strusses, a hydraulic jack capacity of 3 tons, and a chain package with hooks to hang the load. Method of this research is a library research as main sources to design the device. Outcome of this research is a design of lifting device for maximum lifting capacity of 400 k. Material of hook is steel carbon S45C with a maximum tensile stress of 13.26 kg/mm2 . Lifting chain is made of steel alloys Grade 80 with a maximum tensile stress of 187.37 N/mm2 . Truss is selected made of carbon steel S30C with a maximum compress stress of 442.47 kg/cm2 and all of the working stresses are below the allowable stress limits, thus the device is safe to be used.Key words: lifting, Design, Hydraulic